2005
DOI: 10.1124/jpet.105.085076
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human 5-Hydroxytryptamine Type 3AB Receptors by Volatile Anesthetics and n-Alcohols

Abstract: Functional 5-hydroxytryptamine type 3 (5-HT 3 ) receptors can be formed by 5-HT 3A subunits alone or in combination with the 5-HT 3B subunit, but only the 5-HT 3A receptor has been previously studied with respect to the modulation by volatile anesthetics and n-alcohols. Using two-electrode voltage-clamp, we show for the first time the modulation of heteromeric human (h)5-HT 3AB receptors, expressed in Xenopus oocytes, by a series of n-alcohols and halogenated volatile anesthetics. At twice their anesthetic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 35 publications
(50 reference statements)
3
45
0
Order By: Relevance
“…Similarly, our previous work with 5-HT 3AB receptors using a submaximal (EC 10 ) concentration of 5-HT showed that at 2 MAC, chloroform (121%) induced more current enhancement than halothane (43%), whereas isoflurane induced no appreciable current enhancement (Stevens et al, 2005a). Consistent with those results, the present study using receptorsaturating concentrations of DA as agonist found that chloroform induced more channel gating enhancement than halothane, whereas isoflurane did not enhance gating.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, our previous work with 5-HT 3AB receptors using a submaximal (EC 10 ) concentration of 5-HT showed that at 2 MAC, chloroform (121%) induced more current enhancement than halothane (43%), whereas isoflurane induced no appreciable current enhancement (Stevens et al, 2005a). Consistent with those results, the present study using receptorsaturating concentrations of DA as agonist found that chloroform induced more channel gating enhancement than halothane, whereas isoflurane did not enhance gating.…”
Section: Discussionsupporting
confidence: 81%
“…Studies using a range of 5-HT concentrations demonstrate that for 5-HT 3A receptors, the presence of small, halogenated anesthetics significantly reduces the EC 50 for 5-HT without increasing the maximal response to 5-HT (Stevens et al, 2005b). However, this anesthetic-induced reduction in agonist EC 50 is greatly attenuated when 5-HT 3B subunits are incorporated to produce heteromeric 5-HT 3AB receptors (Stevens et al, 2005a). The present study sought to define the underlying mechanism accounting for the difference in anesthetic-induced sensitivity to agonist between the two 5-HT 3 receptor subtypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship to Other Ion Channels-Resembling the pharmacological profile of K-Shaw2, the ionotropic 5-HT3 receptor also exhibits differential dual modulation by inhaled anesthetics (16,20,(42)(43). However, these anesthetics appear to interact with this receptor in a non-competitive manner and the anesthetic effect correlates with the molecular size of the drug used.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 3 receptors are widely distributed in both the central and peripheral nervous system and are involved in the physiologic and pathologic processes that mediate nausea, vomiting, peripheral nociception, and central antinociception [5,20]. Previous studies have shown that inhalation anesthetics modulate 5-HT 3 receptors [25,26]. Sevoflurane is a halogenated inhalation anesthetic.…”
Section: Introductionmentioning
confidence: 99%